Pomiar efektywności kosztowej banków komercyjnych uczestniczących w fuzjach i przejęciach - Korzeb, Zbigniew (Measuring cost efficiency of commercial banks participating in mergers and acquisitions, 2008)
The article aims to analyze the existing econometric approaches to the measurement of the cost efficiency in commercial banks participating in mergers and acquisitions. Transactions of mergers and acquisitions fit into the market economy theory, according to which mergers and acquisitions of commercial banks are a method of reallocating resources within the economy in order to increase their efficiency. The thesis, however rational, is difficult to confirm and cannot be empirically supported. Despite intense research efforts, there is no consensus on the best method or set of methods for measuring cost efficiency. Although - due to the individual character of mergers and acquisitions - it is possible to document improved efficiency in individual transactions, it is difficult to present evidence for a clear and permanent trend of increased cost efficiency in the mergers and acquisitions conducted in the banking sector so far.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 199-206